Intellectual property rights and the governance of international R&D partnerships - Hagedoorn, John; Cloodt, Danielle; van Kranenburg, Hans (Journal of International Business Studies, 2005)
This paper studies the degree to which country differences in intellectual property rights protection affect the choice of companies for a particular mode of international inter-firm R&D partnering. It focuses on the preference of companies for either an equity joint venture or a contractual partnership. We find that international differences in intellectual property rights protection are a significant factor: with less secure protection, firms choose R&D joint ventures rather than contractual partnerships. The level of technological change in industries has an inverse effect on the preference for international R&D joint ventures.